Adolescent social media citizenship - Thomas, Jana (Kansas State University, 2019)
The rise in popularity of mobile technology and social media platform use among today’s adolescents have fueled the need for technology and citizenship education that helps students not only navigate and reduce potential risks, but also take advantage of the benefits of having these social tools literally in the palm of their hand. Digital citizenship education focusing on social media is necessary for student social, emotional and academic growth in the 21st century. The present study continues the efforts of media and education scholars working to define and measure digital citizenship, while at the same time exploring a more narrowed focus of citizenship behavior on the platforms adolescents use most – social media. Previous studies have shown digital citizenship to be a valid and reliable multi-dimensional construct that can be measured using respondent digital technology behaviors, therefore this study takes a multi-factor approach to adolescent social media citizenship, identifying nine dimensions grounded in media uses and gratifications research on adolescent social media behavior and scholarly discourse on traditional and digital citizenship. To test the social media citizenship construct, 440 middle school and high school students between the ages of 11 and 18 self-reported their social media preferences and use behaviors in the areas of (a) digital harassment; (b) psychological health and well-being; (c) social media shopping; (d) security and safety; (e) misuse of technology; (f) communication and conflict management; (g) problem-solving and collaboration; (h) media literacy; (i) digital identity management. Exploratory factor analysis identified underlying relationships within two factors, suggesting a mix of 30 protective and proactive behaviors that have the potential to unlock higher levels of social media citizenship. The study also suggests that factors such as student age, gender, time spent on social media, preferred platform, reason for social media use, and frequency of parent connectivity contribute significantly to a student’s social media citizenship behavior. The results of this study can be used to help parents and educators identify and prioritize educational opportunities, as well as create timely and relevant social media citizenship discussions and support materials.
Keywords: Social media; Digital citizenship; Education; Adolescent; Teens; Parent involvement